Social Loyalty Behavior in Digital Banking Usage: The Role of E-Service Quality, E-System Quality, and Social Trust - Noviana Indriastuti; Kurniawati Darmaningrum; Atik Lusia (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this study is to examine the effect of e-service quality, e-system quality, and e-trust on e-loyalty among users of the Wondr By BNI digital banking application in Surakarta, using a quantitative approach and multiple linear regression analysis. Methodology: This study employed a quantitative survey method using a structured questionnaire based on a five-point Likert scale. Data were collected from 160 Wondr By BNI application users in Surakarta. Multiple linear regression analysis was conducted using IBM SPSS Statistics version 23 to examine the relationships among variables. Main Findings: The results indicate that e-service quality, e-system quality, and e-trust have positive and significant effects on e-loyalty among Wondr By BNI application users. E-trust shows the strongest influence on e-loyalty. Simultaneously, the three variables significantly affect e-loyalty, with an adjusted R² value of 0.710, indicating substantial explanatory power of the model. Within the digital social context, these results emphasize the crucial role of public trust in strengthening long-term user relationships with digital banking platforms. Furthermore, enhanced e-loyalty has broader socio-economic implications, as it supports sustainable digital banking adoption, promotes financial inclusion, and reinforces public confidence in the digital financial ecosystem. Novelty/Originality of this study: This study offers early empirical evidence on user e-loyalty toward the newly launched Wondr By BNI application, released in July 2024, by specifically examining e-system quality, e-service quality, and e-trust in the Surakarta region. It contributes new regional insights by integrating system quality, service quality, and trust to explain user loyalty in emerging digital banking adoption contexts.